In Absentia Trials and the Right to Defend: The Incorporation of a European Human Rights Principle into the Dutch Criminial Justice System - Stamhuis, Evert F (Victoria University of Wellington Law Review, 2001)
In a case against the Netherlands the European Court on Human Rights gave an interpretation of a provision in the Convention that amounted to the recognition of a defence right that was historically and systematically alien to Dutch criminal procedure. The Dutch criminal justice authorities had to respond to implement that recognition in the domestic justice administration. Besides explaining the intricacies of the Dutch trial in absentia, very often considered in comparative studies to be a rather odd feature of Dutch law, this article provides an interesting demonstration of the process of transplanting foreign legal ideas.